2017
DOI: 10.1021/acscatal.6b03102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co and Ru Intimacy in Fischer–Tropsch Catalysts Using Hollow Carbon Sphere Supports: Assessment of the Hydrogen Spillover Processes

Abstract: Mesoporous hollow carbon spheres (MHCSs) were synthesized (d = 290 nm; carbon shell 20−35 nm), and their hollow morphology was exploited to study the influence of Ru nanoparticle location relative to Co3O4 nanoparticles on the reduction behavior and activity of Co Fischer−Tropsch catalysts. Ru nanoparticles were loaded both inside and outside the MHCS, while Co3O4 particles (ca. Co 15 wt % loading) were loaded on the outside of the MHCS. The use of in situ powder X-ray diff raction (PXRD) and temperaturepro-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 45 publications
6
64
0
Order By: Relevance
“…Phaahlamohlaka et al. found that a greater reducibility at low temperatures and higher Fischer‐Tropsch activity could be obtained when Co and Ru metals were in close proximity . The increased turnover frequency (TOF) based on Ru modified Co catalysts was attributed to the dissociation of CO into carbon and oxygen facilitated by bridge‐type CO adsorption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phaahlamohlaka et al. found that a greater reducibility at low temperatures and higher Fischer‐Tropsch activity could be obtained when Co and Ru metals were in close proximity . The increased turnover frequency (TOF) based on Ru modified Co catalysts was attributed to the dissociation of CO into carbon and oxygen facilitated by bridge‐type CO adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…[31] Phaahlamohlaka et al found that a greater reducibility at low temperatures and higher Fischer-Tropsch activity could be obtained when Co and Ru metals were in close proximity. [32] The increased turnover frequency (TOF) based on Ru modified Co catalysts was attributed to the dissociation of CO into carbon and oxygen facilitated by bridge-type CO adsorption. [33] Despite extensive experimental efforts on illustrating the effect of Ru promoter on the catalytic processes, the complementary atomic-level information on the dynamic structure and morphology change of Co nanoparticles induced by Ru has not been available.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In FTS, hydrogen spillover has been only invoked to explain the role of noble metals (Pt, Ru, Au) as promoters for Co reduction in Co/Al 2 O 3 [15] or Co/C catalysts. [16] During FTS on Co/Al 2 O 3 catalysts, spillover results in more CH 4 and higher TOF due to the cleansing effect of atomic H. [15b] Many factors can promote hydrogen spillover on catalyst surface. The capacity of a carbon support to reversibly store atomic H relies on a number of factors such as accessible surface area, geometric nanostructure, defects, dopants, surface chemistry, surface coverage and the interaction of metal nanoparticles and support.…”
Section: Introductionmentioning
confidence: 99%
“…As proven by many excellent works, the bifunctional catalyst is very attractive in many heterogeneous catalytic reactions, such as F‐T synthesis. The structure of these catalysts should be carefully designed as the bifunctional catalyst is sensitive to the intimacy and interaction between two components . Matching these tandem catalytic reactions with suitable component percentage, reaction conditions, spatial distance is also crucial to success.…”
Section: Discussionmentioning
confidence: 99%